Telaah Komprehensif Penyajian Materi Dan Teknik Evaluasi Buku Teks Bahasa Arab Kelas VIII Madrasah Tsanawiyah KMA Nomor 183 Terbitan Kemenag Tahun 2020 - Melly Cahyani; Asep Sunarko; Pamungkas Stiya Mulyani; Fatkhurrohman Fatkhurrohman (Lisanan Arabiya: Jurnal Pendidikan Bahasa Arab, 2023)
The existence of books has a very important role in the learning process, as the saying goes that we are a window of knowledge that we can interpret that by reading books, we will get a lot of knowledge. This study aims to: 1) To find out how the suitability of the presentation of material in the textbook "Arabic Book of the Ministry of Religious Affairs of the Republic of Indonesia 2020" in class VIII Madrasah Tsanawiyah with the demands of the characteristics of the KMA curriculum Number 183 of 2019; 2) To find out how learning evaluation techniques through the textbook "Arabic Book of the Ministry of Religious Affairs of the Republic of Indonesia 2020" in class VIII Madrasah Tsanawiyah. This thesis uses a qualitative research approach with the type of research being bibliographical. For data collection using documentary study methods and online data search. As for analysis, researchers use content analysis methods and discourse analysis, namely in-depth discussion of content. The results of this research analysis show that: Arabic Book Class VIII Madrasah Tsanawiyah Published by the Ministry of Religion in 2020 reference from KMA Number 183 of 2019, presented three Arabic language skills. Then it is added with two supplementary materials. The material is presented in order such as from easy to difficult, simple to complex, and from general to specific. The balance of the amount of material presented is not even, so the presentation in the textbook can be said to be less balanced. Evaluation techniques in textbooks include three areas of assessment, namely the cognitive domain, the affective domain, and the psychomotor domain. The exercises provided are one language competence, but this textbook has not presented a comprehensive evaluation activity at the end of each chapter to hone student competence. Keywords: Textbook, Presentation Technique, Evaluation Technique